A Magnetic Iron Oxide/Polydopamine Coating Can Improve Osteogenesis of 3D‐Printed Porous Titanium Scaffolds with a Static Magnetic Field by Upregulating the TGFβ‐Smads Pathway. Issue 14 (16th June 2020) - Huang, Zhenfei; He, Yu; Chang, Xiao; Liu, Jieying; Yu, Lingjia; Wu, Yuanhao; Li, Yaqian; Tian, Jingjing; Kang, Lin; Wu, Di; Wang, Hai; Wu, Zhihong; et al.
Abstract: 3D‐printed porous titanium–aluminum–vanadium (Ti6Al4V, pTi) scaffolds offer surgeons a good option for the reconstruction of large bone defects, especially at the load‐bearing sites. However, poor osteogenesis limits its application in clinic. In this study, a new magnetic coating is successfully fabricated by codepositing of Fe3 O4 nanoparticles and polydopamine (PDA) on the surface of 3D‐printed pTi scaffolds, which enhances cell attachment, proliferation, and osteogenic differentiation of hBMSCs in vitro and new bone formation of rabbit femoral bone defects in vivo with/without a static magnetic field (SMF). Furthermore, through proteomic analysis, the enhanced osteogenic effect of the magnetic Fe3 O4 /PDA coating with the SMF is found to be related to upregulate the TGF β ‐Smads signaling pathway. Therefore, this work provides a simple protocol to improve the osteogenesis of 3D‐printed porous pTi scaffolds, which will help their application in clinic. Abstract : A new magnetic coating is successfully fabricated on the surface of 3D‐printed titanium scaffolds by codepositing of Fe3 O4 nanoparticles and polydopamine. The magnetic coating endows the composite scaffold with good magnetic responsive performance. It can improve new bone formation in the scaffold with/without the combination of a static magnetic field.